Evolution of enzyme functionality in the flavin-containing monooxygenases - Bailleul, Gautier (2023)
Among the molecular mechanisms of adaptation in biology, enzyme functional diversification is indispensable. By allowing organisms to expand their catalytic repertoires and adopt fundamentally different chemistries, animals can harness or eliminate new-found substances and xenobiotics that they are exposed to in new environments. Here, we explore the flavin-containing monooxygenases (FMOs) that are essential for xenobiotic detoxification. Employing a paleobiochemistry approach in combination with enzymology techniques we disclose the set of historical substitutions responsible for the family’s functional diversification in tetrapods. Remarkably, a few amino acid replacements differentiate an ancestral multi-tasking FMO into a more specialized monooxygenase by modulating the oxygenating flavin intermediate. Our findings substantiate an ongoing premise that enzymatic function hinges on a subset of residues that is not limited to the active site core.